Mermaid Syndrome - Siddique, Md Abu Bakkar; Saha, Sudip; Bose, Kallol; Ghorai, Sudipta; Khan, Kalimuddin (Journal of Nepal Paediatric Society, 2019)
We report a case of sirenomelia baby (Mermaid syndrome) born to a twenty three years old female at 37 weeks of gestation. Sirenomelia is characterized by fusion of the lower limbs with absent kidneys, absent external genitalia and other gastrointestinal defects. It results from the failure of normal vascular supply from the lower aorta in vitro, maternal Diabetes mellitus has been associated with caudal regression syndrome and sirenomelia.